Quantitative PCR of Small Nucleic Acids: Size Matters. Issue 12 (26th March 2021) - Lim, Jay Min; Tevatia, Rahul; Saraf, Ravi F.
Abstract: Quantitative dysregulation in small nucleic acids (NA), such as microRNA (miRNA), extracted from minimally invasive biopsies, such as, blood, stool, urine, nose, throat, are promising biomarker for diseases diagnosis and management. We quantify the effect of the extra step of poly(A) ligation for cDNA synthesis and small size of the NA on the limit of quantification (LOQ) of quantitative PCR (qPCR), the gold standard to measure copy number. It was discovered that for small NA, the cycle threshold, Ct that is proportional to ‐log[c], where [c] is the concentration of the target NA exhibits a sharp transition. The results indicate that although the limit of detection (LOD) of qPCR can be in femtomolar range, the LOQ is significantly reduced by well over three orders of magnitude, in picomolar range. Specifically, the study reveals that the PCR product length is the primary reason the limitation on LOQ and is explicitly shown to be an important consideration for primer design for qPCR in general. Abstract : Amplicon length limits the qPCR quantification of small nucleic acids (NA). The limitation of current quantitative PCR methodologies for small nucleic acids quantification is studied using commercial kits. Using pristine molecules, the limit of quantification of small NA is in picomolars which is over three orders of magnitude lower than long mRNA in femtomolars, as expected. The difference is attributed primarily to the size of the amplicon during quantitative PCR reaction.